Implementation Of Activity Program Planning And Budget Accountability In Efforts To Increase The Performance Of State Universities (Case Study at Kupang State Agricultural Polytechnic) - BEREK, Yudithiane Magdalena Florence; KASE, Petrus; ROSARI, Petrus E D (Journal of Governance, Taxation and Auditing, 2022)
The Kupang State Politani Strategic Plan (Renstra) for 2015-2019 is the primary reference in preparing the Work Plan (Renja) and Budget Work Plan (RKA). Therefore each work unit is required to propose and align activities in the Strategic Plan so that it will be more focused and planned in achieving the targets that have been set. However, in its implementation, many obstacles were found in the program and budget preparation process, where some of the processes needed to meet the activity performance indicators previously set in the strategic plan. This research is qualitative, with primary and secondary data collected through interviews, documentation and observation. Then the data collected is analyzed using data analysis techniques from Miles & Huberman consisting of three streams of activities that coincide, namely: data reduction, data presentation, and conclusion/verification. The results of the study found that the accountability of program planning activities and budgets to improve performance at the Kupang State Polytechnic was analyzed using the Process accountability model, namely; (a) fast service to activity program planning and budgeting, (b) responsive to activity program planning and budgeting and (c) low cost to activity program planning and budget has not been fulfilled while for inhibiting factors the accountability of activity program planning and budgeting to improve performance at the Kupang State Politany are; (a) human resource performance, (b) incidental or emergency priority needs that must be used at that time and, (c) leadership changes that can change program planningactivities and budgets at the Kupang State Politani.